Hubungan Kemampuan Matematika dan Kemampuan Fisika Terhadap Hasil Belajar Siswa Pada Materi Termokimia - Pasar Maulim Silitonga; Rudnia Yanita Sitepu (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2022)
This research was conducted to determine whether there is a significant relationship between mathematical skills, physics skills on students' chemistry learning outcomes, as well as the relationship between mathematical skills and physics skills on chemistry learning outcomes. The sample in this study consisted of one class which was taken using a random sampling technique (lottery). The instrument used was a test instrument which consisted of 3 types, namely a math skills test, a physics skills test and a chemistry learning outcome test. Data analysis was performed using simple regression and multiple regression, as well as the correlation test and the coefficient of determination at the significant level α = 0.05. The results showed that there was a significant relationship between mathematical skills and students' chemistry learning outcomes, there was a significant relationship between physics skills and students' chemistry learning outcomes, then it was examined that there was a significant relationship between mathematical skills  and physics skills on students' chemistry learning outcomes. The contribution of mathematical skills and physics skills to student learning outcomes was 74.30%, meaning that 25.70% was the contribution of other factors.